Implementasi Partitioning Around Medoids Pada Visualisasi Penyebaran Penyakit DBD di Sumatera Utara - Fadillah, Wahyu Nur; Rangkuti, Yulita Molliq; Karo, Ichwanul Muslim (Journal of Mathematics, Computations and Statistics, 2023)
This research aims to develop a Geographic Information System (GIS) using the PartitioningAround Medoids (PAM) method in mapping dengue hemorrhagic fever (DHF) cases in North SumatraProvince. DHF has symptoms of high fever, bleeding, and a high mortality rate if not treated quickly.Therefore, mapping DHF cases is very important in efforts to tackle and prevent this disease. The PAMmethod was used in this study to cluster the DHF case data based on similar characteristics. The firstcluster consists of 18 districts/municipalities is a low cluster, the second cluster consists of 3districts/municipalities is a high cluster, and the third cluster consists of 3 districts/municipalities is amedium cluster. The implementation of PAM is done by using the Minkwoski distance calculation methodwhere the application of the distance will be tested with the Silhouette Index on several numbers of clusters.The best number of clusters for PAM implementation is 3 clusters with a Silhouette Index value of 0.5275.